Outcomes from the First European Planetary Health Congress at ARTIS in Amsterdam - Remco Kort; Koen Arts; Josep M. Antó; Matty P. Berg; Gabrielle Cepella; Jennifer Cole; Amarylle van Doorn; Tomás van Gorp; Milo Grootjen; Joyeeta Gupta; Colin Hill; Eva van der Heide; et al. (Challenges, 2023)
The First European Planetary Health Congress, held from 5 to 7 July 2023 at ARTIS in Amsterdam, represented a significant milestone in the global movement of Planetary Health. The event brought together 121 attendees from academia and the private sector dedicated to addressing the impact of human disruptions to natural systems on the well-being of life on Earth. Co-organized by Natura Artis Magistra (ARTIS) and the European Hub of the Planetary Health Alliance (PHA), the Congress featured five workshops: The Future of Planetary Health Cities, Impact through Synergy, Planetary Health Education, Movement Building, and Food and Microbes. Oral presentations addressed the theme of how human health and the health of human civilization depend on the natural environment, including subthemes on Earth, Water, and Food. Additionally, the subtheme of Humans reflected on how humanity can thrive within Planetary Boundaries and how to imagine a prosperous future for all life on Earth. The First European Planetary Health Congress offered a platform for fostering sustainable, just, and equitable societies within ecological limits. Accordingly, ARTIS and the European Hub aim to shape a hopeful future for generations to come.